Tracking inflation on a daily basis - Santiago E. Alvarez; Sarah M. Lein-Rupprecht (Swiss Journal of Economics and Statistics, 2020)
Using online data for prices and real-time debit card transaction data on changes in expenditures for Switzerland allows us to track inflation on a daily basis. While the daily price index fluctuates around the official price index in normal times, it drops immediately after the lockdown related to the COVID19 pandemic. Official statistics reflect this drop only with a lag, specifically because data collection takes time and is impeded by lockdown conditions. Such daily real-time information can be useful to gauge the relative importance of demand and supply shocks and thus inform policymakers who need to determine appropriate policy measures.
Keywords: 330; Daily price index; Scraped online price data; Debit card expenditures; Real-time information